2020
DOI: 10.1186/s13071-020-04024-2
|View full text |Cite
|
Sign up to set email alerts
|

The design and development of a multicentric protocol to investigate the impact of adjunctive doxycycline on the management of peripheral lymphoedema caused by lymphatic filariasis and podoconiosis

Abstract: Background: As new lymphatic filariasis infections are eliminated through mass chemotherapy, previously affected individuals are left with the sequellae, especially chronic progressive lymphoedema. Currently this is managed by careful attention to limb hygiene to prevent infection. Studies over the past 15 years have suggested that the incorporation of doxycycline treatment may arrest or even reverse progression of lymphoedema. Most of this work has been observational or based on small studies, and if this int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 14 publications
(29 reference statements)
0
11
0
Order By: Relevance
“…However, large-scale implementation trials of doxycycline treatment as a cure for filariasis in over 13,000 African participants have determined greater than 90% adherence to treatment and phase II trials have only reported infrequent and generally mild adverse effects during 6-week therapy ( 68 ). Large-scale, multicenter trials are currently commencing to evaluate doxycycline as an antimorbidity therapy for filarial LE ( 69 ). Future clinical trials should also address dose duration and frequency, comparative efficacy of doxycycline versus minocycline, and whether addition of affordable nonsteroidal antiinflammatory drugs, such as ketoprofen, which is currently undergoing clinical assessment for the treatment of postsurgery LE ( 70 ), may be of added benefit, including in contraindicated groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, large-scale implementation trials of doxycycline treatment as a cure for filariasis in over 13,000 African participants have determined greater than 90% adherence to treatment and phase II trials have only reported infrequent and generally mild adverse effects during 6-week therapy ( 68 ). Large-scale, multicenter trials are currently commencing to evaluate doxycycline as an antimorbidity therapy for filarial LE ( 69 ). Future clinical trials should also address dose duration and frequency, comparative efficacy of doxycycline versus minocycline, and whether addition of affordable nonsteroidal antiinflammatory drugs, such as ketoprofen, which is currently undergoing clinical assessment for the treatment of postsurgery LE ( 70 ), may be of added benefit, including in contraindicated groups.…”
Section: Discussionmentioning
confidence: 99%
“…Research into various aspects of LF care has increased and the number of papers focusing on LF patient care in the last 10 y is double the total published in the previous decade. Areas of current research focus include studies of new antibiotic approaches: for example, doxycycline is being considered for its potential to reduce lymphoedema 30 , 31 ; this multicentre trial is using new digital technology for assessing the size of lymphoedema. 32 Other studies underway range from the use of thermography to monitor acute filarial attacks to understanding and treating the mental health needs of patients.…”
Section: Achievements To Datementioning
confidence: 99%
“…Important advances are likely to come as investigators explore mental health 33 and social aspects, develop new skin care therapies and gain a better understanding of the role of systemic agents such as antibiotics. 31 More versatile ways of assessing the success and impact of MMDP activities, including direct assessment of clinical and well-being improvements in patients, will also most likely provide benefit to the overall success of GPELF. One specific area that is a challenge, and which will become a greater challenge in the final stages of GPELF, is the provision of appropriate (usually long-term) care for the most affected and debilitated LF patients and the most serious lymphoedema cases, many of whom have comorbidities.…”
Section: Reaching Success By 2030mentioning
confidence: 99%
“…Currently a large-scale study is under way in six countries to investigate the impact of 6 weeks of treatment with doxycycline added to standard limb hygiene on early stage filarial lymphoedema and podoconiosis. 54 Results will be available in 2021. The rich parallels between skin changes in podoconiosis and LF suggest future opportunities for research into therapeutics that span the interface between these conditions.…”
Section: Prevention and Control Strategiesmentioning
confidence: 99%
“…One current example of integrating podoconiosis with research into other dermatological NTDs is the ongoing clinical trial to investigate the impact of 6 weeks of treatment with doxycycline added to standard limb hygiene on early stage lymphoedema in six sites in Africa and the Indian subcontinent. 54 …”
Section: Prevention and Control Strategiesmentioning
confidence: 99%